An Exposition of the Cognitive Problems in Rescher’s Coherentist Truth Criteriology - Raphael Etuk, Anthony (International Journal of Scientific Research and Management (IJSRM), 2022)
Perhaps the most influential proposals in the recent literature on the problem of truth in epistemology is Rescher’s version of the coherence theory of truth. Daring to save the theory from sinking under the weights of traditional criticisms, Rescher adopts an approach that differs significantly from the traditional way of presenting the theory: He departs from the traditional definitional emphasis to the criterial route in determining truth under coherence considerations; and advances the process of validating coherence on pragmatic grounds. Adopting the expository, analytic and critical approaches of study, this paper takes a critical look at Rescher’s rebranded coherence theory of truth. It concludes with the view that, though Rescher’s theory exhibits some epistemic merits, yet due to certain inherent cognitive problems, it does not meet the demands of rational success either in justifying the coherence theory or resolving the problem of truth in epistemology.